2016
DOI: 10.5603/ait.a2016.0036
|View full text |Cite
|
Sign up to set email alerts
|

APACHE II score predicts mortality in patients requiring prolonged ventilation in a weaning center

Abstract: Background: Little is known about the diagnostic accuracy of the APACHE II scoring system in prolonged mechanical ventilation. The aim of this study was to assess the utility of APACHE II in order to predict in-hospital mortality, length of stay (LOS) and discharge destination of patients in a weaning centre. Methods: The study group included 130 consecutive patients (median age 71 years; IQR 62−77). APACHE II was assessed based on the worst values taken during the first 24 hours post admission. The primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…However, the AUC of the ROC curve for assessing the prognosis of patients based on age alone is only 0.626, and the sensitivity is only 56.45%, so the prognosis is very limited, some studies have even shown that age does not affect the prognosis of patients with intra-abdominal infection. 35 The APACHE II score is a scoring system used to assess the severity of a patient’s condition and estimate the risk of death, 36 , 37 This scoring system is widely used in clinical practice. The higher the score, the more severe the patient’s condition and the higher the risk of death during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…However, the AUC of the ROC curve for assessing the prognosis of patients based on age alone is only 0.626, and the sensitivity is only 56.45%, so the prognosis is very limited, some studies have even shown that age does not affect the prognosis of patients with intra-abdominal infection. 35 The APACHE II score is a scoring system used to assess the severity of a patient’s condition and estimate the risk of death, 36 , 37 This scoring system is widely used in clinical practice. The higher the score, the more severe the patient’s condition and the higher the risk of death during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…However, the AUC of the ROC curve for assessing the prognosis of patients based on age alone is only 0.626, and the sensitivity is only 56.45%, so the prognosis is very limited, some studies have even shown that age does not affect the prognosis of patients with intra-abdominal infection [35] . The APACHE II score is a scoring system used to assess the severity of a patient's condition and estimate the risk of death [36,37] , This scoring system is widely used in clinical practice. The higher the score, the more severe the patient's condition and the higher the risk of death during hospitalization [38] .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between severity of acute illness and longer survival observed by others is likely to reflect shorter term effects which disappear over the years when more important clinical features such as age and comorbidities along with medical stability come to play a bigger role in these patients' survival. 16,38,41 Thus, the use of measures such as the Acute Physiology and Chronic Health Evaluation (APACHE) II or SAPS II which were developed to predict outcomes of acutely ill patients in an ACH are less effective in doing so in chronically critically ill patients in an LTACH, where the complexity of their multiple interacting pathologies poses a particular challenge in measuring the overall acuity of illness.…”
Section: Discussionmentioning
confidence: 99%
“…This index by measuring multiple organ system deficiencies proved to predict accurately both intermediate and long-term clinical outcomes of PMV patients, thus fulfilling the recognized need for an adequately performing measure of the severity of illness in chronically or seriously ill PMV patients. 38,41,42 It is noteworthy that PMV patients in the CIRS group with the lowest score of 25 were distinct by having a greater ability to recover well enough to be no longer considered chronically critically ill and to maintain a reasonable probability of being weaned from mechanical ventilation (MV) support. These low scoring PMV patients had a good prospect of being discharged to a lower level of care including home and to have a better chance of longer survival.…”
Section: Discussionmentioning
confidence: 99%